Hydrogel‐Stiffening and Non‐Cell Adhesive Properties of Amphiphilic Peptides with Central Alkylene Chains. Issue 36 (21st May 2021) - Yaguchi, Atsuya; Hiramatsu, Hirotsugu; Ishida, Atsuya; Oshikawa, Mio; Ajioka, Itsuki; Muraoka, Takahiro
Abstract: Amphiphilic peptides bearing terminal alkyl tails form supramolecular nanofibers that are increasingly used as biomaterials with multiple functionalities. Insertion of alkylene chains in peptides can be designed as another type of amphiphilic peptide, yet the influence of the internal alkylene chains on self‐assembly and biological properties remains poorly defined. Unlike the terminal alkyl tails, the internal alkylene chains can affect not only the hydrophobicity but also the flexibility and packing of the peptides. Herein, we demonstrate the supramolecular and biological effects of the central alkylene chain length inserted in a peptide. Insertion of the alkylene chain at the center of the peptide allowed for strengthened β‐sheet hydrogen bonds and modulation of the packing order, and consequently the amphiphilic peptide bearing C2 alkylene chain formed a hydrogel with the highest stiffness. Interestingly, the amphiphilic peptides bearing internal alkylene chains longer than C2 showed a diminished cell‐adhesive property. This study offers a novel molecular design to tune mechanical and biological properties of peptide materials. Abstract : A comprehensive study on the amphiphilic peptides revealed unexpected effects of inserting an alkylene chain at the center on strengthening β‐sheet hydrogen bonds, providing stiffened hydrogels and diminishing cell adhesion property, which are clearly different from the effects of putting an alkyl tail at an end. This finding offers a novel molecular design to tune mechanical and biological functionalities of peptide materials.